Garrison’s Self-Directed Learning Model: A Qualitative Study With Nascent Entrepreneurs - Ernie Post (Adult Education Research Conference, 2014)
The qualitative phase of this study found four major themes influencing nascent entrepreneurial learning and attrition in a short-term formal learning program: 1) the entrepreneurs’ motivation, 2) the entrepreneurs’ affective experiences, 3) the entrepreneurs’ obstacles contributing to attrition, and 4) the entrepreneurs’ perceptions about the contextual congruency.